Role of Snake Venom in Medicine - Alyari, Melika; Nikandish, Mehrasa; Nakopia, Ani (Caucasus Journal of Health Sciences and Public Health, 2020)
Snake venom is kind of modified saliva secretion which is secreted by the parotid salivary glands that are located on both sides of head, in front of the ear. Venom is injected by the fangs that are modified type of the pointed teeth. There are three main types of snake venom: Cytotoxins which destroy cellular sites, Neurotoxins which destroy nerve tissue, Hemotoxins which effect cardio system and blood. Although the snake venom can be very dangerous for the human body like causing bleeding, kidney failure, necrosis and human death, but nowadays snake venom is widely used in medications. Snake venoms are mixture of enzymes and non-enzymatic proteins, so these components can be used to treatments other disorders. There are various use of venom in heart attacks and strokes by the proteins which dissolve blood clots and break down the plaques which were formed in the arteries. Different snakes are carrying proteins that are used as treatment of different types of cancers by some macromolecules such as the Crotoxin, Ristostatin which induces platelet aggregations and Contortrostatin. Crotoxin is one of the main compounds of the snake venom which has fatal neurotoxic effects but it is used as pharmaceutical application. According to researches it has function of muscle tension therapy, helping the people with blepharospasm that is involuntary tight closure of eyelids, therapy in patients with dystonia and also as therapy in patients suffering from cancer. Contortostatin is one of the snake venom proteins, which has ability to inhibit cancer cell migration in two different cancer models. Another important role of the snake venom in medications is production of anti-venoms. Antivenom is made by collecting venom from snakes and injecting small amounts of it into a domestic animal. Antibodies which are formed in the domestic animal’s blood are collected. Studies showed that snake venom also can have anti-aging effects on the skin. Nowadays there are many researches and works on modifications of the snake venom and positive uses in medical field.